Accident Identification/Prevention Using Arduino based Blink Sensor - Amit Chaurasia*, Km. Ranjana Maddheshiya (International Journal of Advanced Science and Technology, 2020)
This framework plans the area of the mishap caution framework dependent on ARM and GPS. At the point when the mishap happened, the manual and programmed caution can be figured it out. This framework gives technique a one of a kind to check plastered and tired individuals. This framework has a liquor sensor and eye squinting sensor implanted in the vehicles. Even at this point in the starting vehicle of the pilot, the sensors sense the eye squint and inhale the liquor content and then send the indication to the ringer, GSM and LC|D.. The microcontroller receives sensor rates for inspection right now. Should the value of compasses be used, GSM will then send the SMS, signal will produce sound and the LCD will display the message.